A comparative analysis of the characteristics of chronic cervicitis cervix in women of reproductive age - N. V. Mingalyova; J. G. Abramashvili; N. S. Meteleva (Кубанский научный медицинский вестник)
The results of a retrospective comparative analysis of observations of 500 patients of reproductive age with chronic cervicitis cervical ectopic cylindrical epithelium and metaplastic ekzotserviksa (associated and non-associated with human papilloma virus risk high risk) and 100 women with chronic cervicitis in the stratified squamous epithelium. It has been shown that chronic cervicitis with the presence of an ectopic columnar epithelium in the transformation zone ekzotservikse and type I is a fundamentally different form of nosology, unlike chronic cervicitis in the stratified squamous epithelium.